2021
DOI: 10.3399/bjgp.2020.1051
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial stewardship in the UK during the COVID-19 pandemic: a population-based cohort study and interrupted time-series analysis

Abstract: Background. The COVID-19 pandemic has altered the context for antimicrobial stewardship in primary care. Aim: To assess the effect of the pandemic on antibiotic prescribing, accounting for changes in consultations for respiratory and urinary tract infections (RTIs/UTIs). Design and Setting: Population-based cohort study using the UK Clinical Practice Research Datalink (CPRD) (January 2017 to September 2020). Method: Interrupted time series analysis evaluated changes in antibiotic prescribing and RTI/UTI consul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 15 publications
7
42
0
Order By: Relevance
“…Our findings are in line with the analysis showing when taking into account a decreased number of appointments, the number of prescriptions was 6.7% higher than expected (18). They are also supported by the analysis showing that March 2020 was associated with higher antibiotic prescribing, followed by lower rates than predicted between April and August 2020 (20), while the incidence of RTIs decreased (particularly in April 2020) (20,37). Although participants described having a 'lower threshold' for prescribing antibiotics (which may suggest that some were of little/no benefit), it is possible that these prescriptions were appropriate and influenced by patients' presentations (e.g., higher threshold for consulting, presenting later, access issues).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our findings are in line with the analysis showing when taking into account a decreased number of appointments, the number of prescriptions was 6.7% higher than expected (18). They are also supported by the analysis showing that March 2020 was associated with higher antibiotic prescribing, followed by lower rates than predicted between April and August 2020 (20), while the incidence of RTIs decreased (particularly in April 2020) (20,37). Although participants described having a 'lower threshold' for prescribing antibiotics (which may suggest that some were of little/no benefit), it is possible that these prescriptions were appropriate and influenced by patients' presentations (e.g., higher threshold for consulting, presenting later, access issues).…”
Section: Discussionsupporting
confidence: 90%
“…Studies from primary care in England have shown an overall decrease in antibiotic prescribing during 2020 compared to pre-pandemic (18)(19)(20)(21)(22)(23); with similar trends identified in Scotland (24), Northern Ireland (25) and other countries (26)(27)(28)(29). However, one study of UK data noted an initial increase in antibiotic prescribing in March 2020 before prescribing levels dropped below those expected (with the lowest rate in May) (20).…”
Section: Introductionmentioning
confidence: 77%
“…For the first pandemic wave, similar decreases in presentation and antibiotic prescribing for respiratory tract infections were found in a population-based cohort study in the UK, although in the UK, the initial increase in presentation was temporarily accompanied by an increase in antibiotic prescribing [ 16 ]. In Wales, the pandemic resulted in a significant reduction in dispenses of antibiotics commonly used for treatment of respiratory tract infection in the first wave, whereas dispensing of antibiotics primarily used for urinary tract and skin infections remained stable like in our study [ 17 ].…”
Section: Discussionmentioning
confidence: 67%
“…A prospective audit survey of consultation and management characteristics of patients with respiratory tract infections early in the first pandemic wave in 16 European countries showed that the proportion of patients prescribed antibiotics varied considerably between countries, and was generally lower during the pandemic as compared with the months before, except in Greece, Poland, and United Kingdom (UK) [15].…”
Section: Comparison With Other Literaturementioning
confidence: 99%
“…[1][2][3][4][5][6][7] In regions with high rates of SARS-CoV-2 infection, such as Europe and the United States, there have been reductions in community antibiotic prescribing following the introduction of COVID-19 restrictions in early 2020. [8][9][10][11][12][13][14] However, the underlying data are difficult to interpret as they reflect differing contributory and contemporaneous factors, including variation in public health restrictions and social policies, health care access, increasing use of telehealth and rates of SARS-CoV-2 infections.…”
Section: Introductionmentioning
confidence: 99%